Чисельне дослідження процесів лазерної термообробки системою точкових рухомих джерел тепла - Фуніков, А. С. (ХНУРЕ, 2024)
The study considers the problem of calculating the temperature field in a flat plate during thermal laser treatment using a system of moving point heat source. The R-function’s method in combination with the Galerkin method for non-stationary problems is proposed to solve the problem. A computational experiment was conducted for a rectangular region using test parameter values.
Keywords: рівняння теплопровідності; метод R-функцій